Education HUB. Nomadic embassy of Manifesta 12 in Palermo - Viviana Trapani; Michele Cammarata (Agathón)
The design for cultural events, with specific skills in temporary set-up and communication devices, is today a field of experimentation of co-design strategies for social innovation in urban contexts. On the occasion of Manifesta 12, the Nomadic Biennial, which in 2018 elected Palermo as its seat, the urban dimension has been a laboratory of multidimensional design experiments; the Education Hub project, Manifesta’s ‘nomadic embassy’ in the urban outskirts, was centered on design and developed with a multiplicity of actors, in different parts of the city.  The experience is read through the work of young designers with specific technical and creative potentialities, which also assume the role of mediators between project and context.